ANALISIS DAMPAK COVID-19 PADA SEKTOR PARIWISATA DI PULAU LOMBOK PROVINSI NUSA TENGGARA BARAT - Harjito; Haryandi (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2022)
The Covid-19 pandemic that occurred in Indonesia starting in March 2020 affected the tourism sector of West Nusa Tenggara Province, especially Lombok Island where the business of transportation services, hotels, restaurants, and other businesses declined sharply due to travel restrictions and established protocols. The purpose of this study is to identify the impacts that occur on the tourism sector and identify the strategies of local governments and business actors in overcoming the spread of Covid and reducing its impact on the tourism sector. This study uses a qualitative descriptive method using observations, interviews, and secondary data. The results showed that the impact of the Covid-19 pandemic on the tourism sector of Lombok Island, West Nusa Tenggara was very significant in terms of foreign and domestic tourist arrivals which decreased drastically, hotel occupancy decreased to around 20% from the previous 47%, workforce reduction of 15,000 people, level of hospitality, and other business impacts. Efforts made by the government and tourism businesses to reduce the impact of the Covid-19 pandemic in the tourism sector include the promotion and marketing of tourism, the Gemilang I, II, and III Social Safety Net (JPS) programs involving IKM/MSMEs, logistics certainty and vaccinations. to reduce health risks due to Covid-19, and plan national and international events to attract tourists to return to Lombok Island, West Nusa Tenggara.